Profile of prime minister Japan (Tokyo, 1980)
The book takes a look at the new prime minister's political philosophy and the directions he aims to take, by describing his childhood, his switch to the political career, his activities within the conservative party, together with the contents of some of the speeches he made after beomming prime minister.